Answer:
Step-by-step explanation:
For each consecutive year after that, their profit increased by 12%. The growth is exponential. We would apply the formula for exponential growth which is expressed as
A = P(1 + r)^t
Where
A represents the profit made after t years.
t represents the number of years.
P represents the initial profit made.
r represents rate of increase.
From the information given,
P = 2.4 × 10^6
r = 12% = 12/100 = 0.12
t = 4 years
Therefore,
A = 2.4 × 10^6(1 + 0.12)^4
A = 2.4 × 10^6(1.12)^4
A = 3776446.5